1983
DOI: 10.2136/sssaj1983.03615995004700060014x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pelleting, Temperature, and Soil Type on Mineral Nitrogen Release from Poultry and Dairy Manures

Abstract: Pellets are produced from manures for more convenient and economical use. The rate of N mineralization of manures under different conditions is of agronomic importance, since it allows estimation of mineral N supply to plants as a function of time. Pelleted manure may have mineralization characteristics differing from those of its raw components due to the high temperatures and pressure involved in the pelleting process. The rate of N mineralization of raw manures and pelleted manure was studied in water and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
72
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 0 publications
1
72
1
Order By: Relevance
“…Because C mineralization is theoretically related to N mineralization (Castellanos and Pratt 1981;Gale and Gilmour 1986) we also included C mineralization in our study. As far as N mineralization is concerned, our data differ from those reported by Hadas et al (1983), who noted more rapid initial N mineralization in soils amended with non-pelletized than with pelletized PM during the first week of incubation, whereas concentrations of N mineralized became similar for both manures during the rest of their study. Hadas et al (1983) suggest that pelletization reduces the quantity of readily biodegradable compounds which may be due to (1) reduction in surface area of pellets compared with untreated PM or (2) the high temperature (70°C) exposure during pelletizing compared with those observed during composting of manures (Paré et al 1998).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Because C mineralization is theoretically related to N mineralization (Castellanos and Pratt 1981;Gale and Gilmour 1986) we also included C mineralization in our study. As far as N mineralization is concerned, our data differ from those reported by Hadas et al (1983), who noted more rapid initial N mineralization in soils amended with non-pelletized than with pelletized PM during the first week of incubation, whereas concentrations of N mineralized became similar for both manures during the rest of their study. Hadas et al (1983) suggest that pelletization reduces the quantity of readily biodegradable compounds which may be due to (1) reduction in surface area of pellets compared with untreated PM or (2) the high temperature (70°C) exposure during pelletizing compared with those observed during composting of manures (Paré et al 1998).…”
Section: Discussioncontrasting
confidence: 99%
“…Concentrations of NH 4 + -N were higher in soils amended with T-PM and T-PM + NPK than other treatments during the first 30 d of incubation, and this trend persisted up to 60 d in soil amended with T-PM + NPK. Hadas et al (1983) reported that net NH 4 + -N mineralized increased in soils amended with pelletized PM rather than non-pelletized PM. They also noted that NH 4 + -N concentrations were higher during incubation with PM than with dairy manure because of the higher levels of NH 4 + -N in PM (Hadas et al 1983).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations